K-wave simulation to understand the photoacoustic signal characteristics from various shapes of nanoparticles - Verawaty (2015)
Current attempts in understanding the photoacoustic signal characteristic of various shapes of nanoparticles is mostly performed through numerical simulations. However these computational methods are very time consuming, costly and complicated. Thus there is a need for an easy and fast simulation technique to understand the photoacoustic signal generated from various shapes of nanoparticles. k-Wave is a MATLAB based simulation toolbox to simulate photoacoustic signal given the initial pressure distribution of the target object. In this work, we used k-Wave simulation to understand the photoacoustic signal generated from various shapes of nanoparticles. Seven shapes of nanoparticles are created mainly sphere, cylinder, hollow cylinder, cube, hollow cube, triangle, and star. A point sensor (ultrasound detector) is used to detect the photoacoustic waves generated from different shapes of nanoparticles. The photoacoustic signal generated by different shapes of nanoparticles is captured and processed for further analysis to see their frequency content.